The Evaluation of the Impact of Implementing Organizational Culture on Employee Innovative Behavior - Handayani, Widya; Pendrian, Okder (International Journal of Law Policy and Governance, 2023)
Purpose – This research explores the impact of organizational culture on innovative behavior at PT XYZ, a multinational motorcycle manufacturing company. The goal is to understand how the company's organizational culture contributes to fostering innovative behavior among its employees, ultimately helping PT XYZ maintain its competitiveness in the business environment. Methodology/approach – Using qualitative methods, data were collected through interviews with employees and supported by secondary sources. Findings – The findings reveal that PT XYZ's organizational culture positively influences innovative behavior through initiatives like "Innovation Day" and collaboration with change agents. Factors like knowledge, leadership, appreciation, opportunity, and Key Performance Indicators also contribute to employee innovation. The study highlights challenges related to idea generation, generational differences, and operational issues. Novelty/value –  The research suggests further investigation into these challenges and their connection to employee innovation, as well as the relationship between innovative behavior and work unit performance. Overall, this study emphasizes the importance of organizational culture in promoting innovation and maintaining competitiveness in the business environment.